SOE Dichotomy: Reconciling Public Obligations and Corporate Governance in Indonesia, Malaysia, Singapore - Regina Naya Cahyani (Yayasan Cahaya Generasi Positif, 2026)
The resurgence of state capitalism through state-owned enterprises and sovereign wealth funds has provoked profound doctrinal tension between public accountability and corporate governance. In Indonesia, the dogmatic classification of separated state wealth fundamentally undermines the business judgment rule, exposing corporate directors to criminal liability for commercial losses. Similarly, government-linked corporations in Malaysia suffer from entrenched political appointments that inflate agency costs. Utilizing a comparative doctrinal methodology, this article evaluates the institutional restructuring under Indonesian laws number one and sixteen of 2025 regarding the Danantara investment agency. It argues that without definitive legislative harmonization providing a safe harbor clause, the structural ambiguity will perpetuate managerial paralysis. To reconcile this public-private legal dichotomy, this article proposes transplanting the Temasek model from Singapore. By instituting strict competitive neutrality and dual constitutional control mechanisms, nations can effectively insulate commercial discretion from political intervention while preserving the fiduciary integrity of public asset management frameworks worldwide.